2009
DOI: 10.1002/wnan.61
|View full text |Cite
|
Sign up to set email alerts
|

Complex mathematical models of biology at the nanoscale

Abstract: Mathematical modeling of nanobiosystems is an exciting and rapidly growing new field of research that offers the potential to guide and improve technological developments in both nanomedicine and nanobiomaterial science. Unlike the more traditional fields of science and engineering, however, models of nanobiosystems are notoriously complex. In this paper, we highlight some of the primary sources of complexity in nanobiosystems. In particular, we focus on complexity that arises from the inherent nonlinearity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Bewick et al 101 have reported on the complexity arising from the inherent characteristics of natural biological systems. These include their heterogeneity, their multiscale space-time interactions, the noise generated in physical systems at the nanoscale, the strong coupling between processes that occur at different scales, and the challenging dimensionality size of data needed to represent typical biological systems.…”
Section: Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Bewick et al 101 have reported on the complexity arising from the inherent characteristics of natural biological systems. These include their heterogeneity, their multiscale space-time interactions, the noise generated in physical systems at the nanoscale, the strong coupling between processes that occur at different scales, and the challenging dimensionality size of data needed to represent typical biological systems.…”
Section: Modelingmentioning
confidence: 99%
“…These include their heterogeneity, their multiscale space-time interactions, the noise generated in physical systems at the nanoscale, the strong coupling between processes that occur at different scales, and the challenging dimensionality size of data needed to represent typical biological systems. 101 Jaramillo-Botoro et al 102 have suggested the typical components of a nanomedical model in terms of a five-level theoretical hierarchy: (1) quantum mechanics to determine electronic states, (2) force fields that result from averaging the electronic states and thereby obtaining atom-based forces, (3) simulations of atomic interactions based on force fields, (4) mesoscale or course-grained descriptions that average over many atoms, and (5) continuum mechanics using distributed properties for membranes, cells, tissues, and organs.…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational chemistry is a powerful tool to design, model, simulate, and visualize nanomaterials (Gao, 2001) and nanoparticles, such as dendrimers (Belting and Wittrup, 2009;Diekmann and Lindhorst, 2002;Newkome and Shreiner, 2007;Selim and Lee, 2009) Computer-assisted nanomolecule design has emerged from recent advances in computational chemistry and nanotechnology and is considered well suited for assisting the experimental community in the design of new nanostructures (Bewick et al, 2009). The major advantage of computational nano-design is that it provides a relatively inexpensive and rapid way to explore many structural designs, including the study of stability and prediction of properties (Shapiro et al, 2008).…”
Section: New Challenges For Bioinformatics and Computational Chemistrmentioning
confidence: 99%
“…Thus, the in silico modeling of NPs can assist in targeting and filling gaps in knowledge on the effects of these particular particles [6]. Computational models of the behaviour of NPs in biological systems [7] can be highly valuable in screening candidate particles for potential biomedical use in diagnostics, imaging and drug delivery. Chemically modified carbon nanotubes can act as nanoneedles easily crossing biological barriers and penetrating a variety of cell types [8,9].…”
Section: Introductionmentioning
confidence: 99%